Healthy Air for Children - Er Ding (A+BE: Architecture and the Built Environment)
In response to the WHO and UN’s call to ensure children’s right to breathe “clean” air and the challenges posed by the COVID-19 pandemic on maintaining healthy indoor air quality (IAQ), this PhD research explores ventilation and air cleaning strategies to control the spread of infectious respiratory particles (IRPs) in school classrooms. The study follows four key steps: (1) a literature review bridging school ventilation regimes, IRP transmission, and advanced ventilation systems; (2) a field study to evaluate real-world ventilation and thermal conditions during the pandemic; (3) an experimental investigation of performance of mobile air cleaners (MACs) followed by an in-situ validation; and (4) a combined experimental and computational study to assess personalized air cleaners (PACs) as localized exhaust for IRP removal.